KRISTALISASI NILAI SOCIAL SELF-IMAGE ANAK USIA DINI MELALUI REALISASI MEDIA DIGITAL ETNOPEDAGOGIK BUDAYA SUNDA SEBAGAI UPAYA PENGEJAWANTAHAN FUNGSI PENDIDIKAN ANAK USIA DINI DI PROVINSI JAWA BARAT ERA SOCIETY 5.0 - Gilar Gandana; Edi Hendri Mulyana; Kholby Abqorisa; Rifki Ahmad Fauzi (Universitas Pendidikan Indonesia (UPI), 2022)
Digital media is a fundamental part of early childhood education facilities in the era of the industrial revolution 4.0. Along with the development of the times, the concept of fulfilling the needs of human life is also growing. This is inseparable from the need for future educational facilities. The anxiety that arises in the education aspect is nothing but the inculcation of Indonesian traditional values in the era of society 5.0. Indonesia is a multi-cultural country. One of the cultures that tends to be dominantly inhabited by the Indonesian people is Sundanese culture, precisely in the province of West Java. One of the values built in the Sundanese culture is penance, compassion, and parenting. Various efforts continue to be made in order to achieve the hope of a decent future life. One logical and realistic effort to deal with this anxiety is the application of ethnopedagogic digital media as an early childhood education facility in the era of society 5.0. In line with the results of research conducted related to the application of Sundanese culture-based ethnopedagogic digital media for early childhood in the province of West Java, the City of Bandung increased by 31.4%; Bandung Regency increased 50.4%; Purwakarta Regency increased by 37.4%; and Kota Tasikmalaya increased 38.9%. The research data shows a significant effectiveness in increasing the social self-image value of early childhood 5-6 years in West Java Province with an average increase of 40%.Media digital menjadi bagian fundamental dalam fasilitas Pendidikan anak usia dini di era revolusi industry 4.0. Seiring berkembangnya zaman, maka semakin berkembang pula konsep pemenuhan kebutuhan hidup manusia. Hal tersebut tidak terlepas dari kebutuhan fasilitas Pendidikan masa depan. Kecemasan yang muncul dalam aspek Pendidikan tiada lain adalah penanaman nilai tradisi Indonesia di era society 5.0. Indonesia adalah negara multi budaya. Salah satu budaya yang cenderung dominan dihuni oleh masyarakat Indonesia adalah budaya Sunda tepatnya di provinsi Jawa Barat. Salah satu nilai yang dibangun dalam budaya sunda adalah silih asah, silih asih, dan silih asuh. Berbagai upaya terus dilakukan demi tercapainya harapan kehidupan masa depan yang layak. Salah satu upaya logis dan realistis untuk menanggani kecemasan tersebut yaitu penerapan media digital etnopedagogik sebagai fasilitas Pendidikan anak usia dini di era society 5.0. Sejalan dengan hasil penelitian yang dilakukan terkait penerapan media digital etnopedagogik berbasis budaya sunda untuk anak usia dini di provinsi Jawa Barat, Kota Bandung meningkat 31,4%; Kabupaten Bandung meningkat 50,4%; Kabupaten Purwakarta meningkat 37,4%; dan Kota Tasikmalaya meningkat 38,9%. Data penelitian tersebut menunjukan efektivitas yang signifikan dalam meningkatkan nilai social self-image anak usia dini 5-6 tahun di Provinsi Jawa Barat dengan rata-rata peningkatan 40%.